Think Pair Share sebagai Strategi Efektif dalam Pembelajaran Membaca Intensif Siswa SMP - Astiti Aryasih, Made (Journal of Education Action Reseach, 2018)
The purpose of writing this action research was to improve the results of intensive reading learning for class VII A4 students of SMP Negeri 3 Sawan through the application Think Pair Share learning strategies. Referring to the problems that will be addressed through research, the type of research used is classroom action research through two cycles with stages; planning, implementation, observation, and reflection. The data collection method is a test to answer the question of discourse. The data analysis method is descriptive. The results obtained from this study are the TPS strategy can improve intensive reading skills in students. It is evident from the learning outcomes achieved in intensive student reading. In the initial reflection the average score of students' intensive reading was 73.08 with 38.46% completeness, and in the first cycle, the average rating of students increased to 76.73 with 72.00% completeness even though it was still in the sufficient category, but there was an increase in the average student score is 3.65%. After the improvement of actions in cycle II, the average score of intensive reading of students in the second cycle of 80.77 increased by 4.04% from Cycle I and was in good category and all students complete. The conclusion from this study is that the application of Think Pair Share learning strategies can improve the results of intensive reading learning for class VII A4 students of SMP Negeri 3 Sawan.